Faktor-Faktor Yang Mempengaruhi Kinerja Bank BCA Syariah (Pemberdayaan SDM, Motivasi Kerja Dan Perubahan Organisasi) - Erizal Nazaruddin; Utama Melisha Hidayat; Mutiara Citra Sari; Widia Khairani; Abdul Hafid (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The purpose of this scientific article is to review the concept of factors that influence BCA Syariah performance (Y), HR empowerment (X1), work motivation (X2), organizational change (X3). For human resource management (HR) literature studies, the method for writing scientific articles is to use qualitative methods and literature studies or library research. The results of this article's literature study found that 1. HR empowerment (X1) influences the performance of BCA Syariah Bank (Y), 2. Work motivation (X2) influences the performance of BCA Syariah Bank (Y), 3. Organizational changes (X3) influence BCA Syariah Bank performance (Y).